(untitled) (Research, Society and Development, 2022)
The objective of this study was to evaluate, with the help of the elbow width, the body complexion of patients with heart diseases admitted to an Intensive Care Unit (ICU), located in a city in the state of Bahia. This is a cross-sectional, descriptive study, involving patients with heart diseases admitted to an ICU. In the first 72 hours of admission were analyzed: socio-demographic data, life and health habits, and anthropometric indicators (height, body mass, body mass index (BMI), arm circumference (AC), calf circumference (CC)). To evaluate body complexion (BC), elbow width was analyzed. Anthropometric data were analyzed and classified according to the literature. Data expressed as mean ± standard, with a 5% significance level. Thirty-two patients (23 men and 9 women) were analyzed. Majority: black race/color, with low education, income, sedentary, with arterial hypertension. Anthropometry, AC (low reserve among elderly men and women), BMI (low weight among elderly men and women), CC (low reserve among elderly men and women), BC (medium among men and small among women). No significant correlation was observed between BC vs. age, AC, body mass, BMI and CC. Nutritional risk was observed in the study among elderly men and women. Body complexion, assessed with the aid of elbow width, was classified as small among women.